The Role of the Senkaku (Diaoyu) Islands Dispute in Sino-Japanese Relations - Burešová, Hana; Garlick, Jeremy; Havlová, Radka, 1975-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
The Senkaku/Diaoyu islands are a group of uninhabited rocks in the East China Sea. The dispute for the territorial sovereignty over them openly began between China and Japan in 1968, when ECAFE released findings of massive oil and gas reserves underneath the disputed waters. The dispute is also connected with overlapping claims to exclusive economic zones and to present day remains unresolved. This thesis examines legal justifications of Chinese, Taiwanese and Japanese claims, incidents resulting from the dispute and their effect on Sino-Japanese relations, modern day development and prospects of a peaceful resolution.
Vedoucí práce: Jeremy Alan Garlick
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: mezinárodní studia - diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses